2010
DOI: 10.1124/mol.110.063867
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Neuron-Specific Mas-Related Gene-X1 Receptors Resist Agonist-Promoted Endocytosis

Abstract: Human sensory neuron-specific mas-related gene X1 receptors (hMrgX1s) belong to the superfamily of G protein-coupled receptors (GPCRs), bind cleavage products of pro-enkephalin with high affinity, and have been suggested to participate in pain sensation. Murine or rat MrgC receptors exhibit high similarities with hMrgX1 in terms of expression pattern, sequence homology, and binding profile. Therefore, rodents have been used as an in vivo model to explore the physiological functions and pharmacodynamics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…Regarding the MRGPR-X1 subtype, one rodent receptor activated by BAM8 -22 was identified in mice and rats (MRGPR-C) (1, 2). However, apart from common high affinity binding to BAM8 -22, rodent MRGPR-C and human MRGPR-X1 exhibit fundamental differences in their affinity to other endogenous peptides, as previously reported (4,52,53). Furthermore, in contrast to rodent MRGPR-C, human MRGPR-X1 resist ␤-arrestin-dependent, agonist-promoted endocytosis (4), not only affecting signal duration but also directing GPCR-promoted signaling toward distinct signaling pathways (54).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Regarding the MRGPR-X1 subtype, one rodent receptor activated by BAM8 -22 was identified in mice and rats (MRGPR-C) (1, 2). However, apart from common high affinity binding to BAM8 -22, rodent MRGPR-C and human MRGPR-X1 exhibit fundamental differences in their affinity to other endogenous peptides, as previously reported (4,52,53). Furthermore, in contrast to rodent MRGPR-C, human MRGPR-X1 resist ␤-arrestin-dependent, agonist-promoted endocytosis (4), not only affecting signal duration but also directing GPCR-promoted signaling toward distinct signaling pathways (54).…”
Section: Discussionmentioning
confidence: 88%
“…Recently, Mas-related G protein-coupled receptors-X1 (MRGPR-X1) 2 have been shown to be exclusively expressed in primary sensory neurons and to be activated by bovine adrenal medulla peptide-8-22 (BAM8 -22) originating from proteolytic cleavage of pro-enkephalin by pro-hormone convertases (1,2). Several studies reported activation of the G q pathway by MRGPR-X1 in overexpression systems (1,(3)(4)(5), and a recent study revealed increased pain sensation in 15 healthy volunteers after BAM8 -22 application (6). In contrast, overexpression of MRGPR-X1 in rat dorsal root ganglia (DRG) neurons resulted in BAM8 -22-mediated inhibition of voltage-gated calcium currents and activation of M-type potassium channels via G i/o proteins believed to blunt pain perception (7).…”
mentioning
confidence: 99%
“…How the surface expression of these receptors is downregulated in an activity-dependent manner has been very well characterized (Calebiro et al, 2010;Premont and Gainetdinov, 2007;Shenoy and Lefkowitz, 2011). However, some other GPCRs such as GABA B receptor remain relatively stable at the cell surface even after prolonged agonist treatment (Benke, 2010;Chu et al, 1997;Nantel et al, 1993;Schreff et al, 2000;Solinski et al, 2010). GABA is the primary inhibitory neurotransmitter in the mammalian CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, phosphorylation-deficient mutants of CD88 are resistant to desensitization (Pollok-Kopp et al, 2007). Solinski et al (2010) showed that MrgX1 is one of the few GPCRs that does not associate with ␤-arrestin and is resistant to agonist-induced receptor internalization. Thus, the possibility that MrgX2 receptor is also resistant to agonist-induced phosphorylation, ␤-arrestin recruitment, and desensitization remains to be determined.…”
Section: Discussionmentioning
confidence: 99%